(untitled) (Update Dental College Journal, 2019)
New materials are being introduced to address the need for restoring both carious and non carious (caused by a combination of abrasion, erosion and abfraction) lesions. In an era when more and more patients are retaining their natural dentition, the need for this restoration is increasing. The ideal materials should be adhesive, tooth colored and abrasion-resistant Materials and Methods: Seven disc samples of Compomer, Giomer & Composite restorative materials were prepared for measurement of compressive strength. Results: The value of Compressive strength of Giomer becomes high in comparison to Compomer but not significant in comparison to Composite. Update Dent. Coll. j: 2019; 9 (2): 36-39